The effect of high penetration of wind power on primary frequency control of power systems - Motamed, Bardia (My University, 2013)
In this work, a power system with wind power units and hydro power units are considered. The hydro power unit and variable speed wind turbine are modeled in Matlab/Simulink. The wind turbine has a pitch controller to be used during high wind speed range. The behavior of grid frequency and hydro power are analyzed when there is a power imbalance. Also the effect of increasing wind power penetration on frequency is investigated. Short-term extra active power, inertia emulation and direct pitch angle regulation as a primary frequency control are added to the wind turbine to improve frequency behavior and temporary minimum frequency when there is a mismatch between load and generator. In addition, the combination of these three primary frequency control methods are evaluated. Simulation results show that using primary frequency control methods could be useful to improve the grid frequency behavior when there is a power imbalance in case of high wind power penetration level. The temporary minimum frequency of Inertia emulation method is higher than two other methods. Also the combination of temporary extra active power method and inertia emulation method has the highest value of temporary minimum frequency, although it is slower than other proposed methods.
Keywords: Elkraftteknik; Electric power engineering